PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA VIDEO TERHADAP TINGKAT PENGETAHUAN REMAJA TENTANG PERSONAL HYGIENE SAAT MENSTRUASI - Ferita Yumaeroh; Dwi Susanti (MEDIA ILMU KESEHATAN, 2019)
Background: : The behavior of hygiene during menstruation period is crucial to be conducted by women as it aims to maintain self-cleanliness and self-health both physically and mentally. Women having low personal hygiene behavior consider that cleanliness is trivial. Objective: It aims to find out the influence of health education through video toward the adolescent’s knowledge level on personal hygiene during menstruation period. Methods: This research applied pre-experimental research method with one group pretest-posttest design. There were 125 female students already having menstruation selected as the respondents, the sample collection technique used stratified random sampling. The data analysis used Wilcoxon Signed Rank Test. Results: The adolescent’s knowledge level of female students on personal hygiene during menstruation period before given health education was categorized in low category. Meanwhile, the adolescent’s knowledge level of female students on personal hygiene after given health education was categorized in good category. Hence, there is an influence of health education on the adolescent’s knowledge level on personal hygiene during menstruation period in SMP N 1 Gamping. Conclusion: There is an influence of health education toward the adolescent’s knowledge level on personal hygiene during menstruation period in SMP N 1 Gamping.